Implementasi Sistem Pengambilan Keputusan Mahasiswa Berprestasi Politeknik LP3I Kampus Tasikmalaya - Paramarta, Vip; Nindy, Nindicka Nurul Fadilah; Haerunnisa, Indah; Liana, Lia; Wahyudi Ria, Jan (POLITEKNIK LP3I, 2023)
Being an achievement student is a matter of pride for yourself, your parents and those around you. Becoming an achievement student will equip you to improve each individual's abilities and be able to compete in facing global challenges. All students have the same right to participate in the achievement student selection program. Therefore, in a university it is best to select the best students in an open and transparent manner. Selection of achievement students is also a form of appreciation from universities for students. To minimize errors in selection, it is necessary to have a system as a tool. The Decision Support Systems (DSS) for selecting achievement students at the LP3I Polytechnic Tasikmalaya Campus is assessed by Grade Point Average (GPA) with 4 criteria, namely formative, attendance, assignments, midterm exam and final exam.